Peasant Perceptions of Environmental Remediation Developed by Consorcio Santo Toribio in the Peasant Community of Cari Cari - Mañazo - Puno, 2020 – 2024 - Choqueapaza-Jimenez, Principe; Apaza-Chino, Julian; Apaza-Ticona, Jorge; Quea-Gutierrez, Lucio; Calderón-Torres, Alfredo; Pérez-Quispe, Agustín; Laricano-Flores, Ernesto (Journal of Ecohumanism, 2025)
The research addresses the perceptions of the peasants of the community of Cari-Cari - Mañazo, province and department of Puno, about the environmental remediation carried out by the Santo Toribio Consortium. These actions were carried out to mitigate the effects of the environmental liabilities generated by the former Aladino VI Mining Unit, which operated in the area until 1986 in the Quearaya annex. The main objective was to systematize the population's perceptions regarding the recovery of ecosystem services in the areas affected by copper mining. The methodology used was qualitative, descriptive-ethnographic, non-experimental-longitudinal design, using the inductive method. To collect the information, observation guides and in-depth interviews were applied. The results highlight the effects of mining environmental liabilities in the community, 24 passive components were identified, including a mine entrance, as a legacy of the mining activities of the former Aladino VI Unit. Within the framework of Law No. 28271 of 2004, which regulates mining environmental liabilities (PAMs), the company Activos Mineros S.A.C. (AMSAC) commissioned the consulting firm CESEL S.A. to design a closure plan for these liabilities and the Santo Toribio Consortium assumed the responsibility of executing the environmental rehabilitation, in the project called "Recovery of ecosystem services of the middle part of the Chactani Gorge of the Ilpa Basin". These activities took place between August 10, 2020 and 2024. In conclusion, the research highlights the importance of environmental rehabilitation actions and their impact on the perception of community members, who value the efforts made to restore ecosystem services in their community, after years of negative impact from mining.